AND-subtraction detection modified SNR equation for optical CDMA systems in PON applications - Hmud, Ihssan Sh.; Hasoon, Feras N.; Hatim, Fuad A.; Ghazi Zahid, Ali Z.; Shaari, Sahbudin (Oficyna Wydawnicza Politechniki Wrocławskiej, 2010)
In this paper, AND-subtraction detection scheme compatible with OCDMA system and EDW code was simulated. The aim of the simulation is to adjust the AND-subtraction detection SNR equation for better accuracy in passive optical network (PON) applications. The simulation is performed by (optisys 06) software. The software considered the entire possible practical effects during implementation, such as dispersion, nonlinear effect of the fiber and attenuation of the fiber. The simulation results compared to the analytical results were based on SNR and BER mathematical equations. The comparison shows that the analytical equation should be modified so that the received power (Psr) be more accurate for PON applications.
Optica Applicata, Vol. 40, 2010, nr 1, s. 49-55
Keywords: optyka; optical code-division multiple access (OCDMA); EDW code; AND-subtraction detection scheme; passive optical networks (PON)